Anesthesia for oral surgeries during the COVID-19 pandemic - Sheila N Myatra; Sushan Gupta; Prathamesh S Pai (Wolters Kluwer Medknow Publications, 2020)
The severe acute respiratory syndrome corona virus 2(SARS-Cov2) virus replicates in the nasal cavity, nasopharynx, and the oropharynx. During oral surgery, the risk of viral transmission is high during instrumentation in these areas, while performing airway management procedures, the oral surgery itself, and related procedures. During the corona virus disease 2019 (COVID-19) pandemic, patients with an oral pathology usually present for emergency procedures. However, patients with oral cancer, being a semi-emergency, may also present for diagnostic and therapeutic procedures. When elective surgeries are resumed, these patients will come to the operating room. In asymptomatic patients, the false-negative rate can be as high as 30%. These patients are a source of infection to the healthcare workers and other patients. This mandates universal precautions to be taken for all patients presenting for surgery. Lesions along the airway, distorted anatomy secondary to cancer therapy, shared airway with the surgeon, surgical handling of the airway and the risk of bleeding, make airway management challenging in these patients, especially while wearing personal protective equipment. Airway management procedures, oral surgery, use of cautery, and other powered surgical instruments in the aero digestive tract, along with constant suctioning are a source of significant aerosol generation, further adding to the risk of viral transmission. Maintaining patient safety, while protecting the healthcare workers from getting infected during oral surgery is paramount. Meticulous advance planning and team preparation are essential. In this review, we discuss the challenges and recommendations for safe anesthesia practice for oral surgery during the COVID-19 pandemic, with special emphasis on risk mitigation.